Medial Plantar Artery Flap for Reconstruction of Weight-bearing Sole Defect- A Series of Ten Cases - Sanjay Gordhanbhai Vaghani; Ganesh Sadashiv Chaudhari2 (International Journal of Anatomy Radiology and Surgery, 2023)
Weight-bearing areas of feet are at risk of developing ulcers due to various reasons like a neuropathic foot in diabetes mellitus, acute trauma, post-tumour excision etc., Various reconstructive options have been described in literature from split-thickness skin graft to free flap. This case series reports 10 patients with sole defects. Out of 10 patients, seven patients had heel defect and three patients had the plantar aspect of the forefoot defect. For patients with heel defect, authors used a proximally based medial plantar flap as a reconstructive tool while for forefoot sole defect distally based (reverse) Medial Plantar Artery (MPA) flap was used. The most common cause of heel defect was postdebridement defect in diabetic foot in five cases, postmelanoma excision defect in three cases, postsquamous cell carcinoma excision defect in one case and postelectric burn defect in one case. Flap size ranged from 5x5 cm to 10×7 cm. All flaps offered stable, durable, and cosmetically acceptable skin cover. No patient had a recurrent ulcer during follow-up period. Partial flap necrosis in one case was managed conservatively. The MPA flap offers excellent cover which is a sturdy, durable, cosmetically acceptable cover for medium size defect over the sole i.e., the weight-bearing part of forefoot and heel.